A biblioteca escolar no processo de ensino-aprendizagem: estudo de caso da rede de ensino do município de Vila Velha, Espírito Santo - Rodrigues, Patrícia Nogueira (2023)
Access to information in a planned and organized manner enables individuals to have more autonomy and the criticality they need to search, select, and use information throughout their lives. Therefore, it is essential that schools have a library that is managed, organized, and a place that facilitates the teaching-learning process. Given the above, this study has the general objective of analyzing the potential of school libraries in Vila Velha, Espírito Santo State, crossing data with the results of the Ideb (2019), of the 5th years of elementary school I, to investigate whether the library and its respective services and activities offered by librarians have a relationship with the score of the subject of Portuguese Language of the curriculum component that relates to the score obtained by the school. In this sense the specific objectives are: describe the activities that are developed to enhance reading, writing and interpretation of texts that are necessary for the subject of Portuguese Language; present the collaborative work of the librarian with the teacher; point out the role of the librarian as a mediator in the teaching-learning process; demonstrate the impacts of the use of the library, in a planned way, in the Ideb results. The research methodology adopted was exploratory and documental, the analysis of the results was carried out with a qualitative and quantitative approach and the case study of the library network of the Vila Velha municipal government. A bibliographic survey was carried out in the Reference Database of Journal Articles in Information Science (BRAPCI) and in the Brazilian Digital Library of Theses and Dissertations (BDTD), books, official documents and norms in education and librarianship. As for the field research, a Google Forms questionnaire was used as a data collection instrument. For data analysis, Bardin's content analysis method was used. The results indicate that the library has relevance in the teaching-learning process, however, for the use of the library to make sense and bring learning, the collaborative work of the librarian with the teacher should be planned, developing activities and projects that contribute to enhance what was learned in the classroom, favoring the Ideb results.